An open‐label, phase 1, randomized, three treatments, three‐period, crossover, relative bioavailability study of CC‐292, a potent and orally available inhibitor of bruton tyrosine kinase. (20th March 2022) - Cheng, Yiming; Liu, Liangang; Xue, Yongjun; Zhou, Simon; Li, Yan
Abstract: What is known and objective: CC‐292 is a potent, selective, orally administered small molecule inhibitor of bruton tyrosine kinase (BTK). The aim of this study was to evaluate the relative bioavailability of newly developed CC‐292 tablet formulation (P22 tablet (P22‐TAB) and CC‐292 capsule formulation (P22 capsule [P22‐CAP]) compared to the current CC‐292 capsule formulation (P1 capsule [P01‐CAP]). Methods: This was an open‐label, randomized, three‐period, crossover study in healthy subjects ( N = 12). Blood samples for pharmacokinetics (PK) assessment were collected up to 48 h postdose during each treatment period. Safety was evaluated throughout the study. Results and discussion: For all three formulations, following administration of CC‐292 at a dose level of 250 mg under fasted conditions, CC‐292 was rapidly absorbed with maximum plasma concentrations (Cmax) occurring at a median of 1.5–1.75 h (Tmax). P22‐CAP formulation showed a similar range of Tmax compared to P01‐CAP and P22‐TAB showed a wider range of Tmax compared to P01‐CAP. Comparable or higher Cmax and AUC0‐∞ were noted for P22‐TAB and P22‐CAP formulations as compared to P01‐CAP formulation. The relative bioavailability (Frel) of the CC‐292 P22‐TAB compared to the P01‐CAP reference formulation was 1.02, and the relative bioavailability (Frel) of the CC‐292 P22‐CAP compared to the P01‐CAP reference formulation was 1.23. In conclusion, CC‐292 was well tolerated when administered as single 250‐mg oral doses of P22‐TAB, P22‐CAP or P01‐CAP in the fasted state in this group of healthy subjects. Given that CC‐292 has shown favourable safety profiles in the current clinical settings, the new formulations (P22‐TAB and P22‐CAP) are similar as the reference formulation (P01‐CAP). Abstract : CC‐292: a potent, selective, orally administered small molecule inhibitor of bruton tyrosine kinase (BTK); P01‐CAB: P01 capsule formulation (reference); P22‐CAP: P22 capsule formulation; P22‐TAB: P22 tablet formulation. This was an open‐label, randomized, three‐period, crossover study in healthy subjects ( N = 12). Following single dose of 250 mg, the relative bioavailability (Frel) of the CC‐292 P22‐TAB compared to the P01‐CAP reference formulation was 1.02, and the relative bioavailability (Frel) of the CC‐292 P22‐CAP compared to the P01‐CAP reference formulation was 1.23. Throughout the study, CC‐292 was well tolerated when administered as single 250‐mg oral doses of P22 TAB, P22‐CAP, or P01‐CAP in the fasted state in this group of healthy subjects. Given that CC‐292 has shown favourable safety profiles in the current clinical settings, the new formulations (P22‐TAB and P22‐CAP) are similar as the reference formulation (P01‐CAP).